The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/ma14154240
|View full text |Cite|
|
Sign up to set email alerts
|

Selective Laser Sintering of PA 2200 for Hip Implant Applications: Finite Element Analysis, Process Optimization, Morphological and Mechanical Characterization

Abstract: Polyamide 12 (PA 22000) is a well-known material and one of the most biocompatible materials tested and used to manufacture customized medical implants by selective laser sintering technology. To optimize the implants, several research activities were considered, starting with the design and manufacture of test samples made of PA 2200 by selective laser sintering (SLS) technology, with different processing parameters and part orientations. The obtained samples were subjected to compression tests and later to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Păcurar et al [ 37 ] was engaged in the study of PA2200 material processed using LPBF technology, where the influence of the fracture surface related to the production parameters displayed using a scanning electron microscope (SEM) was demonstrated. The influence of the energy density on the porosity of a 3D product made of PA_2200 was also studied when the structure was monitored by SEM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Păcurar et al [ 37 ] was engaged in the study of PA2200 material processed using LPBF technology, where the influence of the fracture surface related to the production parameters displayed using a scanning electron microscope (SEM) was demonstrated. The influence of the energy density on the porosity of a 3D product made of PA_2200 was also studied when the structure was monitored by SEM.…”
Section: Resultsmentioning
confidence: 99%
“…In the study [ 37 ], they monitored the effect of laser power on the properties of PA2200 material; they also monitored the positive effect of paraxylene solution on surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the selection criterion of the aforenamed techniques depend on the material properties and applications. 94 Pa˘curar et al 95 were made prosthetic acetabular liner using SLM process (Ø = 69 mm), as shown in Figure 16.…”
Section: Biomedical Importance Of Titanium Based Alloysmentioning
confidence: 99%
“…Figure 16. Medical acetabular made up of Ti-6Al-4V by using SLM technique, reused with permission from Pa˘curar et al95 …”
mentioning
confidence: 99%
“…The authors wish to make the following correction to their paper [1]: Incorrect Title There is an error in the title. The correct title of the article is "Selective Laser Sintering of PA 2200 for Hip Implant Applications: Finite Element Analysis, Process Optimization, Morphological and Mechanical Characterization".…”
mentioning
confidence: 99%